Convenient synthesis of selenyl-indoles via iodide ion-catalyzed electrochemical C–H selenation. Issue 63 (23rd July 2018) - Zhang, Xing; Wang, Chenguang; Jiang, Hong; Sun, Linhao
Abstract : Reported herein is a transition metal- and oxidant-free method for the synthesis of selenyl heteroarenes with diselenides through iodide ion-catalyzed electrolytic selenation. Abstract : Reported herein is a transition metal- and oxidant-free method for the synthesis of selenyl heteroarenes with diselenides through iodide ion-catalyzed electrolytic selenation. This direct C(sp 2 )–H selenation strategy, with reduced environmental impact, provides efficient access to a host of selenyl indoles and some other N-heteroarenes under aerobic and galvanostatic conditions.